Small-molecule targeting hairpin loop of hTERT promoter G-quadruplex induces cancer cell death - Song, Jin H. (Cell Chem Biol, 2019)
Increased telomerase activity is associated with malignancy and poor prognosis in human cancer, but the development of targeted agents has not yet provided clinical benefit. Here we report that, instead of targeting the telomerase enzyme directly, small molecules that bind to the G-hairpin of the hTERT G-quadruplex-forming sequence kill selectively malignant cells without altering the function of normal cells. RG260 targets the hTERT G-quadruplex stem-loop folding but not tetrad DNAs, leading to downregulation of hTERT expression. To improve physicochemical and pharmacokinetic properties, a small-molecule analog, RG1603, was derived from the parent compound. RG1603 induces mitochondrial defects including PGC1α and NRF2 inhibition and increased oxidative stress, followed by DNA damage and apoptosis. RG1603 injected as a single agent has tolerable toxicity while achieving strong anticancer efficacy in a tumor xenograft mouse model. These results demonstrate a unique approach to inhibiting the hTERT that functions by impairing mitochondrial activity, inducing cell death.